Violet LED in Bleaching Non-Vital Teeth: a Case Series - Gontijo, Sávio Morato de Lacerda; Arantes, Fernanda Novais; Barreiros, Ivan Doche; Ferreira, Juvenil Alves Neves Diniz; Novaes Júnior, João Batista; Silami, Francisca Daniele Jardilino (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Objetive: The main of this study was to clinically evaluate the effectiveness of violet LED in bleaching non-vital teeth. Case series: three clinical cases were selected (1, 2 and 3), which showed changes in the colour of specific teeth to shades A2, C4 and B3, respectively. Bleaching was performed over three sessions (one session/week). Each session consisted of 20 applications of violet LED for 60 s, with a 30 s interval between them. After bleaching using violet LED, 35% hydrogen peroxide was applied for 15 min in clinical cases 2 and 3, with continuous irradiation with the violet LED in the last 5 min. The dental bleaching using violet LED resulted in teeth with shades A1, C3 and C2 in clinical cases 1, 2 and 3, respectively. The application of 35% hydrogen peroxide with the violet LED further changed the teeth to shades A2 and C1 in clinical cases 2 and 3, respectively. Conclusions: the protocol used in this case series showed that whitening with a violet LED alone should be restricted to cases requiring small colour changes.